2022
DOI: 10.1101/2022.03.23.485430
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inter-brain coupling reflects disciplinary differences in real-world classroom learning

Abstract: While it is widely acknowledged that different disciplines are associated with distinct characteristics that would require different learning strategies and approaches, how the disciplinary differences are manifested in students' daily learning process remain largely underexplored. The present study investigated the disciplinary differences from the framework of hard and soft disciplines, by recording thirty-four high-school students' EEGs simultaneously in real-classroom settings during their regular Chinese … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 86 publications
1
12
0
Order By: Relevance
“…It is worth noting, however, that there may be different kinds of effective speech. For example, a speaker may seek to (mis)direct listeners toward a different understanding than their own; listeners that are unfamiliar versus experts with a particular topic may experience the same speech very differently 10,14 ; and a speaker may attempt to "meet certain listeners where they are" rather than wrangling all listeners similarly. The methodology we introduce takes into account both LL and SL couplings in a moment-bymoment manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting, however, that there may be different kinds of effective speech. For example, a speaker may seek to (mis)direct listeners toward a different understanding than their own; listeners that are unfamiliar versus experts with a particular topic may experience the same speech very differently 10,14 ; and a speaker may attempt to "meet certain listeners where they are" rather than wrangling all listeners similarly. The methodology we introduce takes into account both LL and SL couplings in a moment-bymoment manner.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of a given narrative has been shown to vary across individuals. Both higher LL neural coupling and higher SL neural coupling have been separately associated with better behavioral estimates of speech comprehension across individuals 4,5,7,[9][10][11][12][12][13][14][15][16][16][17][18] . Individuals performing better in the post-test often showed higher neural coupling with the speaker or other listeners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the strength of the speaker-listener neural coupling was associated with the listener's comprehension of the speech (30)(31)(32), suggesting the speaker-listener neural coupling as the inter-brain neural mechanisms of natural speech comprehension and communication (22,33). In this way, the analysis of speakerlistener neural coupling circumvents the challenges of directly modeling the relationship between neural responses and natural speech (26,34), and holds promise for unravelling the neural foundation of natural speech-in-noise comprehension from an inter-brain perspective (26). Our prior work demonstrated that in young listeners, neural activities of the broad language regions were coupled with the speakers, even in noisy conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies are predominantly conducted in controlled laboratory settings, which may not fully capture the complexities of real-world classroom dynamics, thus limiting their ecological validity (Sonkusare et al, 2019;van Atteveldt et al, 2018). With the development of wearable electroencephalogram (EEG) and guided by the perspective of inter-brain coupling, recent hyperscanning studies have begun to move towards real-world classroom scenarios, primarily focus on inter-brain coupling among students (Chen, Qian, et al, 2023;Chen, Xu, et al, 2023;Davidesco et al, 2019;Dikker et al, 2017). The portability, ease of use, and low operational cost of wearable EEG devices are anticipated to facilitate the longitudinal recording of data in classroom settings, providing a rich, comprehensive description and analysis of learning processes.…”
Section: Introductionmentioning
confidence: 99%